An updated look at food environments and obesity - Araneda, Jacqueline; Pinheiro, Anna Christina; Rodríguez, Lorena (Revista Chilena de Salud Pública, 2020)
The World Health Organization considers obesity to be a serious public health pro¬blem. In Chile, results from the 2016-2017 National Health Survey show that 7 in 10 Chileans are overweight or obese, and according to the Ministry of Education, the prevalence of obesity among children entering elementary school has not dropped below 25%. In the last few years, Food Environments have been widely recognized for their impact on the behavior and the nutritional status of different populations. The principal Food Environments and their conditioning factors have been recently identified in Chile, and this information has been used to elaborate the National Food and Nutrition Policy and the inform guidelines and strategies to modify these environments. The individual and structural measures implemented in Chile have proven relevant, both on a national scale, as well as internationally; nevertheless, the development of instruments to objectively and reliably measure Food Environments is still pending.